Correlation of tissue, blood, and air partition coefficients of volatile organic chemicals. - Paterson, S (1989)
The physical chemical factors controlling partition coefficients between air, water, blood, and various tissues are discussed. It is suggested that improved insights into the relations between partition coefficients, which are frequently expressed as correlations, may be obtained by viewing the partition coefficients as ratios of solubilities or pseudosolubilities. A simple, novel correlation approach is developed and applied to 24 volatile organic chemicals, which enables tissue/blood, tissue/air, and blood/air partition coefficients to be estimated from water solubility and vapour pressure. An illustration is presented in which these solubilities are used to calculate the equilibrium distribution of dichloromethane between air, blood, and various tissues.